Experimental Study On Ferrocement With Coir Fibers - Abhishek G. B., Dr. R. M. Mahalingegowda (International Journal of Advanced Science and Technology, 2020)
Ferrocement is comprised of a blend of concrete mortar and single or various layers work which are firmly separated. It is generally utilized because of its favorable position from its a portion of the conduct, for example, mechanical properties and effect quality. The fundamental point of this task is to explore or consider the quality attributes of Ferro-concrete with and without utilizing coir fiber. By differing the level of fiber included (1%, 2% and 3% of concrete). Likewise contrast the quality of Ferro-concrete and single and twofold layer of square wire work.The mechanical test was performed to check the impact of fibers on improving compressive, flexural and split tensile in Ferro-cement. Since fiber go about as optional fortification, it will keep Ferrocement from small scale splitting and engendering break development and builds the quality. After the expansion of coir strands into ferrocement expands the flexural and spilt elasticity consequently it very well may be utilized more as flexural part in development.